2023
DOI: 10.1007/s00406-023-01580-3
|View full text |Cite
|
Sign up to set email alerts
|

Ulotaront: review of preliminary evidence for the efficacy and safety of a TAAR1 agonist in schizophrenia

Abstract: Ulotaront is a trace amine-associated receptor 1 (TAAR1) agonist in Phase 3 clinical development for the treatment of schizophrenia. Ulotaront was discovered through a unique, target-agnostic approach optimized to identify drug candidates lacking D2 and 5-HT2A receptor antagonism, while demonstrating an antipsychotic-like phenotypic profile in vivo. The mechanism of action (MOA) of ulotaront is thought to be mediated by agonism at TAAR1 and serotonin 5-HT1A receptors. Ulotaront has completed two Phase 2 trials… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 79 publications
0
12
0
Order By: Relevance
“…TAAR1 agonists, including the Phase 3 clinical development candidate ulotaront, have recently emerged as a potential new treatment approach in schizophrenia and other psychiatric disorders including depression, anxiety and substance abuse [ 1 , 59 , 60 ]. Intriguingly, recent preclinical evidence has also identified TAAR1 as a novel regulator of metabolic control and a potential target for obesity and type 2 diabetes [ 16 , 17 , 61 , 62 ].…”
Section: Discussionmentioning
confidence: 99%
“…TAAR1 agonists, including the Phase 3 clinical development candidate ulotaront, have recently emerged as a potential new treatment approach in schizophrenia and other psychiatric disorders including depression, anxiety and substance abuse [ 1 , 59 , 60 ]. Intriguingly, recent preclinical evidence has also identified TAAR1 as a novel regulator of metabolic control and a potential target for obesity and type 2 diabetes [ 16 , 17 , 61 , 62 ].…”
Section: Discussionmentioning
confidence: 99%
“…A population analysis [ 95 ] of the pharmacokinetics of ulotaront based on eight studies concluded that ulotaront shows a good absorption profile and exhibits dose-dependency at 10 to 100 mg. The median time for the maximum concentration and the median effective half-life were estimated to be 2.8 and 7 h, respectively [ 93 ].…”
Section: New Agents For the Treatment Of Schizophreniamentioning
confidence: 99%
“…Trace amine-associated receptor 1 (TAAR1) is a member of the G-protein-coupled receptor (GPCR) TAAR family enriched in the central nervous system and periphery, which could couple to diverse G protein subtypes (G s , G q , and G i1 ) by recognizing a spectrum of different endogenous amine-containing hormones and metabolites (EAHs and EAMs) and has been confirmed to be associated with cognition, mood, antidepressant, and schizophrenia treatment. SEP-363856 was identified as a TAAR1-G s pathway agonist with beneficial effects in MK-801-induced schizophrenia-like rodent models via high-throughput phenotypic behavioral screening . Notably, SEP-363856 did not cause the cognitive impairment and other serious side effects associated with current antipsychotics targeting the D2R or 5-HT2AR. , In 2019, SEP-363856 was granted a breakthrough therapy designation for the treatment of schizophrenia with significant reduction in the Positive and Negative Syndrome Scale (PANSS) total score in clinical trials by the U.S. Food and Drug Administration (FDA). Unfortunately, the once-daily dose of SEP-363856 in acutely psychotic adults living with schizophrenia did not meet the primary end point in two therapeutic effect experiments of phase III.…”
Section: Introductionmentioning
confidence: 99%